(3GdJLGQI GdEdcJQhfjI hCMcGegG aj Gdabg GdESdGejs - (3Ydj eMeO CMeO(B, (3CHh GdYRs ((3YeGf(B:s (3OGQ GdfaGFS ddfTQ hGdJhRjY(B,s, 2013)
(3GdJLGQI GdEdcJQhfjI eaghegG hJcjjagG Gdabgj hCgejJgG hNUGFUgG heNGWQgG heYhbGJgG(B- (3YbO GdJLGQI GdEdcJQhfjI eagheg hCQcGfg hGdBKGQ GdeJQJHI Ydjg(B- (3hSGFd EKHGJ YbO GdJLGQI GdEdcJQhfjIs
Keywords: (3GdJLGQI GdEdcJQhfjIs; (3Gdabg GdESdGejs